PENGARUH PENGETAHUAN MANAJER TENTANG SISTEM INFORMASI AKUNTANSI MANAJEMEN TERHADAP GAYA PENGENDALIAN MANAJEMEN - Widia Astuty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2015)
This study aimed to obtain the interpretation of the contribution of managers’ knowledge influence on management accounting information systems to control style of management.The research method using descriptive and verificative types. The unit of analysis in this study is the national private commercial bank foreign exchange in North Sumatra,and the respondents in the accounting and finance manager. Descriptive analyzes were performed to analyze the object of research. While the verification analyzes conducted to examine the effect of managers’ knowledge about management accounting information systems to control  style of management by Partial Least Square (PLS) methods.The results showed that the bank manager is not currently use an interactive management accounting information, they tend to use the diagnostic style  in management accounting information. Managers who use management accounting information with diagnostics style perceive that management accounting information is limited to  financial information only. Furthermore, the results of this study show that managers’ knowledge on accounting information systems management significantly influence the style of management control. Keywords: Managers’ knowledge of management accounting information, management control